Association of apoptotic marker cytokeratin18 with blood pressure in non-alcoholic fatty liver disease patients - Benash Altaf; Shireen Jawed; Rana Muhammad Tahir Salam (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Non Alcoholic fatty liver disease (NAFLD) associated with hypertension (HTN) is an emerging health issue globally. It is associated with increased levels of apoptotic marker CK18. Main objective of this study was to explore association of cytokeratin18 (CK18) with hypertension (HTN) in NAFLD patients. Methodology: Descriptive cross sectional study was conducted in Mayo hospital Lahore. Hundred NAFLD subjects were enrolled from OPD of radiology department after approval from ethical review committee. Anthropometric measurements were taken and blood pressure (BP) was measured by mercury sphygmomanometer. Blood samples were drawn from each patient for CK18 levels with ELISA. Data was analyzed by SPSS 20. Continuous variables were presented as mean± SD. Association between CK18 and HTN were analyzed by regression analysis and results were presented as ? coefficient. P value<0.05 was taken significant. Results: Mean age of studied subjects was 43.8±5.34 with height (m), weight (kg) and BMI 1.59±0.063 m, 78.2±11.17 kg, 30.5±4.07kg/m2 respectively. Systolic and diastolic blood pressures were 106±12.8, 72± 12.8mmHg. CK 18 was not significantly associated with systolic (P value 0.55) and diastolic BP (P value 0.37) most probably due to small size of study. Conclusion: Most of the NAFLD patients were hypertensive and have raised CK18 levels than normotensive subjects. So, raised levels of CK18 in NAFLD subjects might be helpful in early screening of HTN. However, significant association was not observed probably due to small sample size. Keywords: CVS, CK18, DBP, HTN, MS, NAFLD, SBP (write full forms for all these abbreviations. Continuous...